Demensi Etnik dalam Kerukunan Umat Beragama di Kota Pontianak Provinsi Kalimantan Barat - Arnis Rachmadhani (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2018)
A study of qualitative research with data obtained from interviews, in-depth observation, and literature study was conducted in Pontianak City, West Kalimantan Province, describes the general social interaction in Pontianak City that leads to an associative form of interaction, although there is also a potential that leads to dissociative. Assositive interactions include accommodation in the form of a fairly tolerant attitude of religious life; assimilation in the form of cultural assimilation, especially the assimilation between religion and culture that strengthens the relationship of two things, and which strengthens the relationship between families, where cultural interaction strengthens inter-citizen harmony, especially among religious followers; as well as cooperation in the implementation of cultural activities antaretnik. However, dissociative interactions also occur that is the emergence of competition in the form of contradictions. The social systems in Pontianak influence the harmony between religious and inter-ethnic communities. These social systems are social systems built from ethnic Malay, Dayak, Bugis, Madurese, Javanese, and other ethnic groups. The process of working the social system on interethnic religious harmony in Pontianak City, West Kalimantan Province due to the diversity of ethnic groups that can have positive and negative impacts. Positive influence because strengthening the unity of ethnic intern and its negative influence is able to bring up the problem.